Identification of epsilon-N-mono-, epsilon-N-di-, and epsilon-N-trimethyllysine by high-performance liquid chromatography. - Garcia, R (1986)
Dansyl derivatives of epsilon-N-mono-, epsilon-N-di-, and epsilon-N-trimethyllysine were resolved from other amino acids in proteins by the use of high-performance liquid chromatography. The system was tested with amino acid standard combinations as well as with acid-hydrolyzed proteins known to contain methylated residues. In all cases the methylated lysines were well resolved.